Electronic structure and magnetic properties of graphite intercalated with 3d-metals - Grechnev, G.E.; Lyogenkaya, A.A.; Kolesnichenko, Yu.A.; Prylutskyy, Yu.I.; Hayn, Roland (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
Electronic structure and magnetic properties of graphite-based systems with intercalated 3d-transition metal atoms (V, Cr, Mn, Fe, Co, Ni) were calculated ab initio using the density functional theory. The presence of different magnetic states depending on the type of inserted M atoms is revealed for hexagonal P6/mmm and P63/mmc crystall structures. The values of magnetic moments appeared to be governed by the p–d hybridization, and by variations of exchange interactions with intercalation. The results of calculations clearly indicate itinerancy of the 3d-electrons of inserted M atoms.